ACTUAL PROBLEMS OF APPLYING OF SOME INNOVATIVE TECHNOLOGIES IN THE PROCESS OF CONSIDERATION OF THE APPLICATIONS FOR RECOGNITION AND GRANTING OF PERMISSION FOR COMPULSORY ENFORCEMENT OF FOREIGN JUDGMENTS - Корнієнко, Марина (Київський національний університет імені Тараса Шевченка, 2022)
The article is devoted to the problem of applying certain innovative technologies in the process of consideration by the courts of Ukraine of applications for recognition or granting of permission for compulsory enforcement of foreign judgments. The author analyses the provisions of the Civil Procedure Code of Ukraine that provide for the right of participants in cases to submit documents to the court in electronic form. Actual judicial practice of Ukrainian courts, both local and the Supreme Court, is also analyzed. The article highlights three main problems concerning the right of applicants to apply for recognition or enforcement of foreign judgments in electronic form. The first problem concerns inconsistencies in the provisions of Chapters 1 and 2 of Title IX of the Civil Procedure Code of Ukraine, namely the absence in Chapter 2 of any reference to the right of the applicant to file an application and its attachments in electronic form. The second problem arises from the content of the current edition of part 5 of article 466 of the Civil Procedure Code of Ukraine, which provides for the right to file an application in electronic form, but at the same time sets significant restrictions on the exercise of this right. This provision does not allow applicants to exercise their procedural rights in full and does not reduce the formalization of civil proceedings. The third problem relates to the unequal interpretation by Ukrainian courts of the provisions of civil procedure law and the lack of a unified approach to recognizing the right of applicants to submit documents to the court using the court's official e-mail address. Developing these issues, the author quotes judicial practice, which demonstrates the absence of a sustainable and unified approach and confirms the author's conclusions regarding the above-mentioned problems. Summarizing the research and practical analysis, the author stresses the importance of taking a broad approach to the interpretation of the legislation governing the procedure for filing documents in electronic form, in the current context of martial law in Ukraine. In the conclusion to the article, the author gives practical proposals for solving the three problems identified in the article.

Окреслено основні проблеми, які виникають у процесі застосування окремих інноваційних технологій у разі подання до суду та розгляду клопотань про визнання та надання дозволу на примусове виконання іноземних судових рішень, а також висунення пропозицій для подолання наявних проблем. Використано загальнонаукові та спеціальні наукові методи, зокрема діалектичний метод, метод системного аналізу, дедукції, індукції, синтезу, формально-логічний та догматичний метод тощо. Проаналізовано положення Цивільного процесуального кодексу України, які закріплюють право учасників справ на подання до суду документів в електронній формі. Виокремлено три основні проблеми, які стосуються права заявників на подання клопотань про визнання та надання дозволу на виконання іноземних судових рішень в електронній формі. Перша проблема стосується неузгодженості положень глав 1 та 2 Розділу ІХ Цивільного процесуального кодексу України, а саме – відсутності у главі 2 будь-якого посилання на наявність у заявника права на подання клопотання та додатків до нього в електронній формі. Друга проблема випливає зі змісту актуальної редакції ч. 5 ст. 466 Цивільного процесуального кодексу України, яка передбачає право на подання клопотання про надання дозволу на примусове виконання рішення іноземного суду в електронні формі, але водночас встановлює суттєві обмеження для реалізації цього права. Зазначена норма не дає заявникам можливості реалізувати свої процесуальні права повною мірою та не зменшує формалізованість цивільного процесу. Третя проблема пов'язана з неоднаковим тлумаченням судами України норм цивільного процесуального законодавства та відсутністю єдиного підходу до визнання права заявників на подання документів до суду з використанням офіційної електронної адреси суду. Для розкриття окресленої проблематики наведено підходи місцевих судів та Верховного Суду, які демонструють відсутність сталого підходу та підтверджують висновки автора. Підкреслено важливість застосування широкого підходу до тлумачення законодавства, що регламентує порядок подання документів в електронній формі в умовах воєнного стану, що триває в Україні. Наведено пропозиції щодо розв'язання цих проблем.
АКТУАЛЬНІ ПРОБЛЕМИ ЗАСТОСУВАННЯ ОКРЕМИХ ІННОВАЦІЙНИХ ТЕХНОЛОГІЙ У ПРОЦЕСІ РОЗГЛЯДУ КЛОПОТАНЬ ПРО ВИЗНАННЯ ТА НАДАННЯ ДОЗВОЛУ НА ПРИМУСОВЕ ВИКОНАННЯ РІШЕНЬ ІНОЗЕМНИХ СУДІВ
Keywords: рішення іноземного суду; визнання рішення іноземного суду; звернення судового рішення до примусового виконання; інноваційні технології; Єдина судова інформаційно-телекомунікаційна система; foreign judgment; recognition of a foreign judgment; enforcement of a judgment; innovative technologies; Unified Court Information and Telecommunication System